ANALISIS FAKTOR INTRINSIK YANG BERHUBUNGAN DENGAN KEPATUHAN BEROBAT PASIEN TB PARU: ANALISIS FAKTOR INTRINSIK YANG BERHUBUNGAN DENGAN KEPATUHAN BEROBAT PASIEN TB PARU - Sholichah, Nofiana farhatus; Santoso, Shelfi Dwi Retnani Putri; Prasetyo, Joko (LPPM STIKes Bahrul Ulum Jombang, 2020)
Pulmonary TB is an infectious disease that is still the main health problem in Indonesia. One of the problems in Pulmonary TB is non-compliance with medication. This systematic review sheds light on the relationship of intrinsic factors with the treatment adherence of Pulmonary TB patients. This study aims to analyze intrinsic factors related to the adherence of pulmonary TB patients. The design or research method used in this study is review literature. It uses a systematic review of five electronic databases (Pupmed, Wiley, Sage, ProQues, Google Scholar) for previous research published between 2015-2020. Some of the keywords used include Pulmonary TB, age, gender, education, knowledge, employment, income, distance from health care facilities. The PRISMA Flowchart is used to summarize the article selection process. A total of 32,849 articles were identified. Researchers found 10 articles with inclusion criteria met in reviews. Gender, education, knowledge, occupation, income, distance of health care facilities have a significant relationship with the adherence of pulmonary TB patients Obtained intrinsic factors that have no relationship with the adherence of pulmonary TB patients i.e. age factors. Intrinsic factors that have a significant relationship with the treatment compliance of Pulmonary TB patients are gender, education, knowledge, occupation, income and distance of health care facilities.